Laparoscopic resection of a giant adrenal cyst: a case report - Sapra, Akhilesh; Zafar, Syed; Gudivada, Vijayalakshmi; Somani, Piyush (International Surgery Journal, 2025)
Giant adrenal cysts, often discovered incidentally, are rare lesions. This case report details a patient who had many symptoms, including nonspecific abdominal distension. Imaging tests showed a large cystic growth that was closely connected to the left adrenal gland. No abnormalities were found in routine laboratory and endocrine function tests. Laparoscopic surgery was used, and the cystic mass was entirely removed. Upon pathological inspection, an endothelial structure with vascular components was found in the cyst wall. After extensive evaluation, the lesion was determined to be an angiomatous adrenal endothelial cyst, a very uncommon type of adrenal cyst. This case report aimed to increase awareness of this rare condition.